Parallel Generation of Tetrahedral Meshes with Cracks by Spatial Binary Decomposition - Markos Oliveira Freitas (2015)
This work describes a technique for generating three-dimensional tetrahedral meshes using parallel computing, with shared, distributed, or hybrid memory processors. The input for the algorithm is a triangular mesh that models the surface of one of several objects, that might have holes in its interior or internal or boundary cracks. A binary tree structure for spatial partitioning is proposed in this work to recursively decompose the domain in as many subdomains as processes or threads in the parallel system, in which every subdomain has the geometry of a rectangular parallelepiped. This decomposition attempts to balance the amount of work in all the subdomains. The amount of work, known as load, of any mesh generator is usually given as a function of its output size, i.e., the size of the generated mesh. Therefore, a technique to estimate the size of this mesh, the total load of the domain, is needed beforehand. This work uses a refined octree, generated from the surface mesh, to estimate this load, and the decomposition is performed on top of this octree. Once the domain is decomposed, each process/thread generates the mesh in its subdomain by means of an advancing front technique, in such a way that it does not overpass the limits defined by its subdomain, and applies an improvement on it. Some of the processes/threads are responsible for generating the meshes connecting the subdomains, i.e., the interface meshes, in order to generate the whole mesh. This technique presented good speed-up results, keeping the quality of the mesh comparable to the quality of the serially generated mesh.